Analisis Produktivitas Produksi PT. Karya Pak Oles Tokcer Denpasar - Utari, Putu Mas Krisna; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The purpose of this study was to measure the level of production productivity, analyze the contribution of the productivity ratio component and compile recommendations for productivity improvement at PT. Karya Pak Oles Tokcer, productivity is the ratio of output and input is more directed to the operational aspects in the transformation of inputs into outputs. In this study there are 6 ratios that are used as criteria in measuring productivity, these ratios are included in the criteria of efficiency, effectiveness and infrential. The method used is the Objective Matrix (OMAX). The lowest level of production productivity obtained in November 2018 decreased by -36.2% with a productivity index value of 177.1, while the highest value in February 2018 increased by 87.5% with a productivity index value of 403.0 . Analysis of the contribution of the productivity ratio component to production productivity at PT. Karya Pak Oles Tokcer who received the highest productivity value is a ratio of 3 with a value of 774.9 and the lowest productivity value is a ratio of 6 with a value of 430.9. Proposed improvement of production productivity in the ratio of 1 to 156 hours, ratio 2 of Rp. 14,256,935, ratio 3 of Rp. 535,252,794, ratio 4 of 48 people, ratio 5 of Rp. 4,525,849,355, the ratio of 6 to 152 hours. Keyword: production, productivity, objective matrix (OMAX),  PT. Karya Pak Oles Tokcer